La dimensione interculturale dell’educazione tra metodi narrativi e pratiche autobiografiche - Sirignano, Fabrizio Manuel (Kritik. Rivista di letteratura e critica culturale, 2023)
The redefinition of pedagogical intervention methodologies is necessary in order to adequately respond to the new educational needs derived by the current complex and multicultural society. Of course, there are no universally valid paths and methodologies, but it is necessary to start from an in-depth analysis of the context, above all in order to provide answers that give due weight not only to the content and learning aspects but also to the cognitive, emotional ones and relational. The paper highlights how the autobiographical method, configuring itself as a metacognitive approach, assumes a strong value especially in intercultural education paths. Autobiographical storytelling allows in some way to distance oneself from oneself and one’s own experiences in order to be able to analyze them in a more objective and conscious way. This act allows to establish a bridge between the past and the present, providing cognitive skills to plan one’s future.